Tema,ciri-ciri dan fungsi jaku sema dan jaku silup dalam pengajaran bungai jaku - Elizabeth Janie Silai (Tanjong Malim, 2018)
Tema,ciri-ciri dan fungsi jaku sema dan jaku silup dalam pengajaran bungai jaku by Elizabeth Janie Silai